Sikap Moderasi Beragama Guru Madrasah - Akhmadi, Agus (Balai Diklat Keagamaan Surabaya, 2022)
Religious moderation is a national program to create a peaceful life. The attitude of religious moderation is developed in madrasas as the main values ​​of life. The movement to realize religious moderation in madrasas needs to be started by teachers with an attitude of religious moderation. This study aims to describe the attitude of religious moderation of madrasa teachers and strategies for developing religious moderation in madrasas. The research begins with a literature review to examine the concept of religious moderation, attitudes of religious moderation and educational strategies for religious moderation. The research respondents were 111 madrasa teachers who participated in the training organized by the Surabaya Religious Education and Training Center. Data collection was carried out by means of a questionnaire. The research instrument is in the form of a standardized religious moderation attitude scale, a questionnaire sent via google form upload to respondents. Data processing was carried out by descriptive statistics. The results showed that the religious moderation attitude of madrasa teachers was in the medium and high categories. Teachers' religious moderation attitudes vary in terms of education level, teacher job background, teaching specialization, employment status and gender. The attitude of religious moderation is important in realizing a peaceful life, therefore it is recommended to increase the attitude of religious moderation in teachers.